Reflectance Spectrum of a Color Blue Generated by Curved Multilayer and Iridescent of the Elytron of the Calidea Signata Bug - Ouedraogo, Issaka; Igo, Serge Wendsida; Simonis, Priscilla; Ouedraogo, Alioune; Zeghmati, Belkacem (European Scientific Journal, ESJ, 2016)
This paper focuses on the study of the origins of blue iridescent reflections of the elytron of Calidea Signata, of the pentatomidae family which is commonly known as bug. Indeed, we use the spectrophotometry measurements, scanning electron microscopy characterization technique, and a ray tracing code program combined with the transfer matrices method, to explain the structure which is responsible for the color of the blue reflections and the iridescent effect. Thus, we noticed that the color of the bug as a result of two peaks. The first and main peak is located at 485.5 nm, corresponding to the blue color. The second peak, is less intense at 525 nm, corresponding to the green-blue color. The numerical reproduction of the reflectance spectrum gives 510.25 nm for the main peak, and 539.5 nm for the secondary peak. These results confirm that the multilayer structure is responsible for the blue color of the Calidea Signata bug. Lastly, the curve of the multilayer is responsible for the iridescence.